2006
DOI: 10.1007/s00586-006-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

Wound conditioning by vacuum assisted closure (V.A.C.) in postoperative infections after dorsal spine surgery

Abstract: The use of vacuum assisted closure (V.A.C.) therapy in postoperative infections after dorsal spinal surgery was studied retrospectively. Successful treatment was defined as a stable healed wound that showed no signs of acute or chronic infection. The treatment of the infected back wounds consisted of repeated debridement, irrigation and open wound treatment with temporary closure by V.A.C. The instrumentation was exchanged or removed if necessary. Fifteen patients with deep subfascial infections after posterio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(77 citation statements)
references
References 75 publications
1
68
0
5
Order By: Relevance
“…Most studies reported that the NPWT dressing was placed in theater following debridement 25, 29, 31 or irrigation and debridement 3,4,5,12,19,23,24,26,27,30 of the wound. Only one study reported the use of a non-mechanical debridement method 31 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Most studies reported that the NPWT dressing was placed in theater following debridement 25, 29, 31 or irrigation and debridement 3,4,5,12,19,23,24,26,27,30 of the wound. Only one study reported the use of a non-mechanical debridement method 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical site infection (SSI) 1 and pre-operative radiotherapy 2 are the overwhelming causes of morbidity in post-operative spinal wound complications. SSI rates range from 0.4% to 20% following spinal surgery 1, [3][4][5] . Post-operative incontinence, posterior surgical approach and surgery for tumour resection are additional risk factors for SSI in spinal surgery 6 .…”
Section: Description Of the Conditionmentioning
confidence: 99%
See 3 more Smart Citations